Hubungan Antara Gaya Kepemimpinan dengan Manajemen Konflik pada Karyawan PT Inti Bharu Mas Palembang - Osni Mustika Weni; Rina Oktaviana (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2017)
Study was aimed to determine the relationship between leadership style with conflict management. The population in this study was 120 subjects and sampled was 89 subject. This research used proportional random sampling technique. Researched measuring instruments used the leadership style scale and conflict management scale. Results of the analysis data showed the division of Unilever correlation coefficient (R) of 0.564 with a coefficient of determination (r square) of 0318, as well as the value of p= 0, 0000, then the division of Shell's correlation coefficient (R) of 0,360 with (square r) of =0.397, correlation coefficient in the division of Dua Kelinci (R) of 0.934 with a coefficient determinant (square r) of 0.872. Contribution of independent variables on the dependent variable of 31.8% in the division of Unilever, then 39.7% in the division of Shell, and 87.2% in division of Dua Kelinci.